Crystal structure of poly[[μ(2)-diaqua-diaqua-μ(2)-l-proline-κ(2) O:O′-strontium] dibromide] - Sathiskumar, Selladurai (Acta Crystallogr E Crystallogr Commun, 2015)
In the title coordination polymer, {[Sr(C(5)H(9)NO(2))(H(2)O)(4)]Br(2)}(n), the proline molecule exists in a zwitterionic form with one of the ring C atoms disordered over two sites [site-occupancy factors = 0.57 (6):0.43 (6)]. The Sr(II) ion is nine-coordinated by six water O atoms, two monodentate and two μ(2)-bridging, and three carboxylate O atoms of the proline ligands, with two bridging [Sr—O range = 2.524 (4)–2.800 (5) Å]. In the crystal, there is no direct interaction between the proline molecules. However, the proline and water molecules associate with the bromide counter-anions through a number of intermolecular O—H⋯Br and N—H⋯Br hydrogen-bonding interactions, giving a three-dimensional supramolecular structure.